MODEL PENINGKATAN NILAI PERUSAHAAN MELALUI STRUKTUR MODAL PADA INDUSTRI PERBANKAN DI BURSA EFEK INDONESIA - Rizka Ariyanti (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2016)
This study aims to examine and analyze the increase in the value of the company through its capital structure, asset tangibility, profitability, firm size, liquidity( Studies in Bank Go Public in Indoseia Stock Exchange 2010 -2014 ) To test these variabels, the researchers use the 27 companies that went in public Indosia Stock Exchange. This type of research is explanatory research, Tehknik data collection using documentary technique. The data used in this research are secondary data from financial statetements published by banking companies during 2010 -2014 Furthermore, the data collected was analyzed quantitatively by using multiple regression using Eviews program version 8.1 The result showed that the variables Tangibility simultan assets does not affect the DER, Profitability significantly influence the DER, Firm size significant negative effect on the DER, Liquidity does not affect the DER. While the tangibility of assets, profitability, Firm size affect the PBV. Liquidity does not affect the PBV. DER is found as a mediating variable that strengthen the influence of tangibility assets, Profitabiliy, Firm size, Liquidity on firm value PBV banking companies listed in Indonesia Stock Exchange.